2013
DOI: 10.1021/jp406945u
|View full text |Cite
|
Sign up to set email alerts
|

Jet-Cooled Spectroscopy of the α-Methylbenzyl Radical: Probing the State-Dependent Effects of Methyl Rocking Against a Radical Site

Abstract: The state-dependent spectroscopy of α-methylbenzyl radical (α-MeBz) has been studied under jet-cooled conditions. Two-color resonant two-photon ionization (2C-R2PI), laser-induced fluorescence, and dispersed fluorescence spectra were obtained for the D0-D1 electronic transition of this prototypical resonance-stabilized radical in which the methyl group is immediately adjacent to the primary radical site. Extensive Franck-Condon activity in hindered rotor levels was observed in the excitation spectrum, reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…DF spectra for the four lowest bands in the LIF spectrum are shown in Figure . Because the discharge nozzle constricts the jet expansion, we adopted a large nozzle-laser distance (5 cm, or x / D = 100) to guarantee collision-free measurements. , Our signal-to-noise ratio and spectral resolution (∼25 cm –1 ) under these conditions are modest owing to the diminished radical number density in the laser interaction region, although it was possible to measure portions (bottom of figure) of the origin DF spectrum at higher resolution (15 cm –1 ).…”
Section: Resultsmentioning
confidence: 99%
“…DF spectra for the four lowest bands in the LIF spectrum are shown in Figure . Because the discharge nozzle constricts the jet expansion, we adopted a large nozzle-laser distance (5 cm, or x / D = 100) to guarantee collision-free measurements. , Our signal-to-noise ratio and spectral resolution (∼25 cm –1 ) under these conditions are modest owing to the diminished radical number density in the laser interaction region, although it was possible to measure portions (bottom of figure) of the origin DF spectrum at higher resolution (15 cm –1 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the spin-dependent dynamics is practically a virgin land. Open-shell electronic configuration of radical molecules requires a different, much more complicated approach so that the information concerning the correct solving of vibrational dynamic problem of the species is rather scarce. , Because of this circumstance, in the current study, the open-shell UHF approach, implemented in the AM1 semiempirical tool CLUSTER-Z1, was suggested to solve the spin-dependent vibrational dynamic problem of highly radicalized graphene oxyhydride molecules I–IV, whereas molecules V–VIII are considered in the framework of the DMol 3 approach.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although the electronic spectra of the three xylyl radicals have been the subject of several previous studies, only very recently was the electronic spectrum of α-methylbenzyl radical reported, and nothing is known about the optical spectroscopy of the methyltropyl radical. With respect to the xylyl radicals, excitation spectra to the first excited state (Ã ← X) have previously been reported in the visible region by Fukushima and Obi and Miller and co-workers .…”
Section: Introductionmentioning
confidence: 99%